Rethinking African globalisation agenda: Lessons from COVID-19 - Angela Ifeanyi Ujunwa; Augustine Ujunwa; Chinwe Okoyeuzu (Research in Globalization, 2021)
The COVID-19 outbreak resulted in a synchronized disruption of the global economy, globalization agenda, and re-emergence of protectionism. Africa appears to be worse-off by the re-emergence of protectionism despite the increasing debate that globalization tends to increase intra-country inequality and poverty in Africa. We argue that the enormous benefit Africa derived from globalization, especially, during the COVID-19 pandemic, makes it imperative for the African Union to rethink its globalization strategy, as well as strategies to mitigate African economies from the vulnerability of future pandemic. We argue that the vulnerability of African economies to the COVID-19 could be traced to characteristics of African economies, such as the dominance of low-skilled labour force, informally employed workers that do not have the option of working remotely, digital divide due to poor internet penetration, urban and rural structures that promote the spread of a virus, and breakdown of critical global supply chain may. On the basis of the above, we recommend that African Union globalization agenda should focus on promoting massive investment in virtual economic activities; global ecological responsible public policies; a more inclusive policies that promotes access to education. healthcare, and resources; and redesign urban settlement to reduce the spread of diseases.
Keywords: 330; African economic monetary cooperation; Globalisation; Corona virus